2016
DOI: 10.1103/physrevd.94.015032
|View full text |Cite
|
Sign up to set email alerts
|

Leptonicg2moments,CPphases, and the Higgs boson mass constraint

Abstract: Higgs boson mass measurement at ∼ 125 GeV points to a high scale for SUSY specifically the scalar masses. If all the scalars are heavy, supersymmetric contribution to the leptonic g − 2 moments will be significantly reduced. On the other hand the Brookhaven experiment indicates a ∼ 3σ deviation from the standard model prediction. Here we analyze the leptonic g − 2 moments in an extended MSSM model with inclusion of a vector like leptonic generation which brings in new sources of CP violation. In this work we c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 49 publications
1
22
1
Order By: Relevance
“…As an alternative, one can resolve the (g − 2) µ discrepancy by extending the particle content of the MSSM with vector-like (VL) matter, as investigated, e.g., in [29][30][31][32][33][34][35][36][37]. The introduction of VL superfields in the superpotential brings along extra degrees of freedom without spoiling the successful unification of gauge interactions at the GUT scale [38].…”
Section: Contentsmentioning
confidence: 99%
“…As an alternative, one can resolve the (g − 2) µ discrepancy by extending the particle content of the MSSM with vector-like (VL) matter, as investigated, e.g., in [29][30][31][32][33][34][35][36][37]. The introduction of VL superfields in the superpotential brings along extra degrees of freedom without spoiling the successful unification of gauge interactions at the GUT scale [38].…”
Section: Contentsmentioning
confidence: 99%
“…There have been attempts to resolve these tensions, see for example [9][10][11] and references therein. In this paper, we consider U(1) ′ extensions of the MSSM (UMSSM) that can also improve the situation [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…There have also been alternative solutions as for example, adding vector-like (VL) matter to MSSM which has been studied in Refs. [23][24][25][26][27][28][29][30][31][32]. The presence of new VL sector gives extra contribution to (g − 2) µ by introducing new sources of smuon mixing and new Yukawa couplings [32].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of new VL sector gives extra contribution to (g − 2) µ by introducing new sources of smuon mixing and new Yukawa couplings [32]. Apart from (g − 2) µ , it has been shown that VL colored sparticles provide extra contributions to Higgs mass [33][34][35][36][37][38] and several phenomenological analyses have addressed the extra VL matter in the context of various long-standing theoretical issues related to beyond SM physics [23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%